Transcatheter Aortic Valve Implantation with ACURATE neo: Results from the PROGRESS PVL Registry. (25th June 2022) - Kim, Won-Keun; Thiele, Holger; Linke, Axel; Kuntze, Thomas; Fichtlscherer, Stephan; Webb, John; Chu, Michael W. A.; Adam, Matti; Schymik, Gerhard; Geisler, Tobias; Kharbanda, Rajesh; Christen, Thomas; et al.
Abstract : Objectives . The PROGRESS PVL registry evaluated transcatheter aortic valve implantation (TAVI) in patients treated with ACURATE neo, a supra-annular self-expanding bioprosthetic aortic valve. Background . While clinical outcomes with TAVI are comparable with those achieved with surgery, residual aortic regurgitation (AR) and paravalvular leak (PVL) are common complications. The ACURATE neo valve has a pericardial sealing skirt designed to minimize PVL. Methods . The primary endpoint was the rate of total AR over time, as assessed by a core echocardiographic laboratory. The study enrolled 500 patients (mean age: 81.8 ± 5.1 years; 61% female; mean baseline STS score: 6.0 ± 4.5%) from 22 centers in Europe and Canada; 498 patients were treated with ACURATE neo . Results . The rate of ≥ moderate AR was 4.6% at discharge and 3.1% at 12 months; the rate of ≥ moderate PVL was 4.6% at discharge and 2.6% at 12 months. Paired analyses showed significant improvement in overall PVL between discharge and 12 months (P < 0.001 ); 64.6% of patients had no change in PVL grade, 24.9% improved, and 10.5% worsened. Patients also exhibited significant improvement in transvalvular gradient (P < 0.001 ) and effective orifice area (P = 0.01 ). The mortality rate was 2.2% at 30 days and 11.3% at 12 months. The permanent pacemaker implantation (PPI) rate was 10.2% at 30 days and 12.2% at 12 months. Conclusions . Results from PROGRESS PVL support the sustained safety and performance of TAVI with the ACURATE neo valve, showing excellent valve hemodynamics, good clinical outcomes, and significant interindividual improvement in PVL from discharge to 12-month follow-up.